Exchange rate policy and devaluation in Malawi - Pauw, Karl; Dorosh, Paul A.; Mazunda, John (International Food Policy Research Institute, 2013)
This study demonstrates why devaluation was ultimately necessary in Malawi and also what its eventual impact might be in terms of prices, income distribution, and domestic production. Our approach is to use a computable general equilibrium (CGE) model to evaluate the economywide impacts of foreign exchange shortages in Malawi under two alternative exchange rate regimes. The foreign exchange shortages are modeled by simulating the effect of actual shocks, including tobacco price declines and reductions in direct budgetary support or foreign direct investments. We then evaluate the economy’s response to these shocks under a fixed exchange rate regime and a flexible exchange rate regime.